The Effect of Marketing Mix on Patient Satisfaction and Their Impact on Patient Loyalty in Hospital Inpatients - Catherine Budiman; Hendra Achmadi (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
Hospital is a health-care institution that provides comprehensive individual health services through continuous service quality improvement and active marketing management. A marketing mix is a set of tools that can be controlled and used by hospitals to influence and create patient satisfaction so that patients become loyal. The marketing mix of the 4Ps (product, price, place, and promotion) can affect patient satisfaction and loyalty. The purpose of this study is to examine the relationship between the marketing mix and patient satisfaction, and its impact on patient loyalty. The type of research is quantitative research with hypothesis testing. This study obtained 165 respondents by filling out online questionnaires from this study and processed using PLS-SEM. The results indicated that the product, price, place, and promotion variables gave an R2 value of 0.519 for patient satisfaction as a mediating variable. The mediating variable successfully showed a positive effect on patient loyalty with R2 0.499 and mediated the impact of the independent variable. Product, price, place, and promotion significantly positively impact patient satisfaction, which then describes a significant positive effect on patient loyalty.